Winning the education World Cup - Abd Razak, Dzulkifli (2010)
THE FIFA World Cup 2010 final that saw Spain becoming the champion for the first time fires the imagination of the public as to what is possible when the playing field is level. Add to this the style of the game displayed by the Spanish team powered by a tactical mental agility that enabled them to outperform the opponent's aggressive harassment and you have a beautiful game.